Cytotoxic and Phytotoxic Activities of Native Brazilian Forest Gabiroba (Campomanesia xanthocarpa Berg.), Fruits, and Flour against Shrimp (Artemia salina L.) and Lettuce (Lactuca sativa L.) - Aiane Benevide Sereno; Carla Dayane Pinto; Luciana Gibbert; Marina Talamini Piltz de Andrade; Michelli Aparecida Bertolazo da Silva; Schaina Andriela Pontarollo Etgeton; Obdulio Gomes Miguel; Josiane de Fátima Gaspari Dias; Claudia Carneiro Hecke Krüger; Iara José de Messias Reason (Foods, 2023)
Gabiroba, a native fruit in Brazil’s Atlantic Forest region, has significant nutritional and therapeutic properties. However, due to its seasonality, consumption by the population is limited. Thus, the development of gabiroba byproducts would add significant value to the food and therapeutic industries. Therefore, it is essential to study and support the lack of toxicity of gabiroba fruit extracts. In the present study, physicochemical analyses of fresh fruits (GF) and dehydrated whole gabiroba flour (WGF) and preliminary toxicity analyses of WGF were performed. The toxicity results showed a microcrustacean LC50 of >1000 mg/mL when exposed to WGF extracts at various concentrations (10–1000 μg/mL; p = 0.062) using the Artemia salina method, with no evidence observed of proliferative activity or toxic metabolic compounds in the WGF extract. The phytotoxicity of WGF using Lactuca sativa L. allowed germination and root growth at various concentrations of WGF extract, with the lowest (100 μg/mL) and highest (1000 μg/mL) concentrations exhibiting 98.3% and 100% seed germination, respectively. In conclusion, these results indicate that the WGF preparation preserved the nutritional and antioxidant potential of gabiroba fruits and that WGF is safe for use as a raw material in the food industry and for therapeutic purposes.